Wpływ przystąpienia Polski do Unii Europejskiej na rozwój handlu zagranicznego artykułami rolno-spożywczymi - Urban, Stanisław (An Impact of the Polish Accession to the EU on the Development of Polish Foreign Trade in Agro-food Products, 2008)
Polish accession to the structure of the European Union has resulted in a considerable increase in Polish contribution, as far as the international trade in agro-food products is concerned. In consequence, a good balance between the Polish and international trade has been notified from 2003 and is still in the increase. As a result, the Polish trade geography has changed. After the accession the Polish agro-food trade mainly with the European Union countries has been developed. The main Polish partner in trade has became Germany but the trade with Russia has fallen down from the first to far position. Furthermore, there is a substantial change in the structure of the Polish foreign agro-food trade. A considerable fall in the trade of plant products has become noticeable, but the trade of animal products is being grown. The trade in row agriculture products has also gone down. However, the trade in highly pro-cessed agro-food products continues to rise.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 44-55